Tight money - tight credit: Coordination failure in the conduct of monetary and financial policies - Julio A. Carrillo; Enrique G. Mendoza; Victoria Nuguer; Jessica Roldán-Pe\~na (Banco de México, 2017)
In a New Keynesian model with the BGG accelerator and risk shocks, we show that violations of Tinbergen's Rule and strategic interaction between economic authorities undermine the effectiveness of monetary and financial policies. Separate monetary and financial policy rules produce higher welfare than a monetary rule augmented with credit spreads. The latter yields a tight money-tight credit regime in which the interest rate responds too much to inflation and not enough to credit. Reaction curves for the policy-rule elasticities are nonlinear, which reflects shifts in these elasticities from strategic substitutes to complements. The Nash equilibrium is inferior to the Cooperative equilibrium, both are inferior to a first-best outcome, and both might produce tight money-tight credit regimes.
Keywords: E44; E52; E58; 330; Financial Frictions; Monetary Policy; Financial Policy